A 6‐day clinical pathway after a pancreaticoduodenectomy is feasible, safe and efficient. Issue 9 (2nd December 2012) - Walters, Dustin M.; McGarey, Patrick; LaPar, Damien J.; Strong, Aimee; Good, Elizabeth; Adams, Reid B.; Bauer, Todd W.
Abstract Background The utilization of post‐operative clinical pathways leads to shorter hospital stays and decreased healthcare costs. This study evaluated patient outcomes after implementation of a 6‐day discharge pathway after a pancreaticoduodenectomy. Methods A post‐operative clinical pathway was developed and implemented for patients undergoing a pancreaticoduodenectomy at the present institution aimed at discharge by post‐operative day six. Patient charts were retrospectively reviewed to determine the rates of adherence to the pathway at each step, readmission and post‐operative complications. Results In total, 113 consecutive patients underwent a pancreaticoduodenectomy, receiving post‐operative care under the clinical pathway guidelines. The median length of stay was 7 days (mode 6 days); 41% of patients were discharged by post‐operative day six, 62% by day seven and 79% by day eight. In univariate analysis, delayed gastric emptying was associated with a delayed discharge after post‐operative day six (P = 0.002). There were no post‐operative deaths and 16% of patients required readmission within 30 days of discharge. In univariate analysis, obesity was the only variable associated with an increased rate of readmission (P < 0.001). Discussion Clinical pathway utilization after a pancreaticoduodenectomy allows a high percentage of patients to be discharged within a week and is associated with a low rate of readmission. Clinical pathway implementation allows for safe and efficient patient care.